Option A:
![(x-5)^{2}+(y-3)^{2}=16](https://tex.z-dn.net/?f=%28x-5%29%5E%7B2%7D%2B%28y-3%29%5E%7B2%7D%3D16)
Solution:
Given data:
Center of the circle is (5, 3).
Radius of the circle = 4
To find the equation of the circle:
The general form of the equation of a circle in centre-radius format is
![(x-h)^{2}+(y-k)^{2}=r^{2}](https://tex.z-dn.net/?f=%28x-h%29%5E%7B2%7D%2B%28y-k%29%5E%7B2%7D%3Dr%5E%7B2%7D)
where (h, k) is the centre of the circle and r is the radius of the circle.
Substitute the given values in the equation of a circle formula:
![(x-5)^{2}+(y-3)^{2}=4^{2}](https://tex.z-dn.net/?f=%28x-5%29%5E%7B2%7D%2B%28y-3%29%5E%7B2%7D%3D4%5E%7B2%7D)
![(x-5)^{2}+(y-3)^{2}=16](https://tex.z-dn.net/?f=%28x-5%29%5E%7B2%7D%2B%28y-3%29%5E%7B2%7D%3D16)
The equation of the given circle is
.
Hence Option A is the correct answer.
Answer:
(-65)/17
Step-by-step explanation:
Evaluate 3/(x - 2) - sqrt(x - 3) where x = 19:
3/(x - 2) - sqrt(x - 3) = 3/(19 - 2) - sqrt(19 - 3)
19 - 3 = 16:
3/(19 - 2) - sqrt(16)
19 - 2 = 17:
3/17 - sqrt(16)
sqrt(16) = sqrt(2^4) = 2^2:
3/17 - 2^2
2^2 = 4:
3/17 - 4
Put 3/17 - 4 over the common denominator 17. 3/17 - 4 = 3/17 + (17 (-4))/17:
3/17 - (4×17)/17
17 (-4) = -68:
3/17 + (-68)/17
3/17 - 68/17 = (3 - 68)/17:
(3 - 68)/17
3 - 68 = -65:
Answer: (-65)/17
Answer:
2x10^3
Step-by-step explanation:
Factor the numerator and denominator and cancel the common factors.
It would be 2/4. 2/4 simplifies to 1/2.